Efektivitas Media Flashcard sebagai Media Edukasi dalam Meningkatkan Pengetahuan Kesehatan Reproduksi pada Remaja - Nur Gilang Fitriana; Ratna Kurniawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Reproductive health is an important component of adolescent health, characterized by various biological, psychological, and social changes. According to the 2017 Indonesian Demographic and Health Survey (IDHS) for adolescents, adolescents’ knowledge of reproductive health remains largely focused on physical changes, such as voice changes in males (76%) and menstruation in females (87.7%). This condition indicates the need for more comprehensive and accessible reproductive health education. This study aimed to determine the effectiveness of using flashcards in improving adolescents’ reproductive health knowledge. The study employed a pre-experimental method with a one-group pretest–posttest design involving 60 respondents. Data were collected using a knowledge questionnaire administered before and after education using flashcards. Data were analyzed using the Wilcoxon test. The results showed an increase in the mean reproductive health knowledge score from 56.35 in the pretest to 88.85 in the posttest. The Wilcoxon test yielded a p-value of < 0.001, indicating a significant increase in knowledge after the educational intervention. Therefore, flashcards are effective as a reproductive health education medium for adolescents because they present information visually in an engaging, simple, and memorable manner.